Influence of Residual Blood on the Physico-chemical characteristics of Beef during Post Mortem Refrigerated Storage : doi: 10.5958/2581-6616.2021.00013.X - Sasidharan, Vandana; Vasudevan, V. N.; Sunil, B.; Sathu, T.; Ramnath, V.; K. J , Arun Sankar; R , Yazhinidevi (Journal of Meat Science, 2022)
Inefficient and improper bleeding causes more blood and subsequently more haemoglobin (Hb) to be retained in the  muscles, which acts as powerful promoters of lipid oxidation and may decrease the shelf life of meat and meat products.  A study was carried out at the Meat Technology Unit, Kerala Veterinary and Animal Sciences University, Mannuthy to  examine the effect of bleeding efficiency on certain physico-chemical characters of muscle samples upon post-mortem  refrigerated storage at 4±1◦C. Muscle samples were collected from imperfectly bled (IB), scientifically slaughtered (SS)  and cold slaughtered (CS) carcasses and were packed in HDPE packages and the pH, lipid oxidation and total viable  count of the muscle samples were evaluated during a six-day post-mortem refrigerated storage at 4±1◦C. The mean Hb  concentration (mg/g) of IB and CS carcasses (0.07±0.003 and 0.09±0.008, respectively) were significantly (p˂0.01)  higher than that from SS carcasses (0.05±0.004). The pH values estimated for IB, SS and CS muscle samples on day 0  and day 6 were 6.35±012 and 5.66±0.035, 6.19±0.104 and 5.93±0.174 and 6.46±0.05 and 5.62±0.07, respectively. The  thiobarbituric acid reacting substances value (TBARS, mg malonaldehyde/kg) increased significantly from 0.34±0.08  and 0.34±0.06 at day 0 to 1.02±0.18 and 0.75±0.05 for IB and CS muscles samples, respectively. The total viable  count (TVC, log cfu/g) significantly increased from 5.29±0.07 and 5.24±0.02 at day 0 to 5.56±0.12 and 5.45±0.06,  respectively for IB and CS muscle samples. No significant difference was found in the TVC and TBARS values for SS  muscle samples. The results revealed that the level of bleeding had no significant influence on the muscle pH on storage  at 4±1◦C, but had effect on the oxidative stability as well as the microbiological quality. The microbiological quality and  oxidative stability of meat samples which underwent complete bleeding were superior to the other samples on all days  of storage. Thus, it was concluded that bleeding levels do affect meat quality. Hence, it can be concluded that higher  levels of residual blood can result in enhanced lipid oxidation and higher total viable count in meat upon storage at  4±1◦C. However, lipid oxidation status and total viable count of cold slaughtered meat were not significantly different  for samples from IB carcasses.
Keywords: Cold slaughter; Imperfect bleeding; Lipid oxidation; Shelf-life